Pengaruh Bermain Lompat Kata Terhadap Kecerdasan Linguistik Anak Usia 5-6 Tahun Di PAUD Salsabila Tembung T.A 2022-2023 - Wena Altia Tendang; Dewi Fitria (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
This study aims to determine whether there is a positive and significant effect of playing jumping words on the linguistic intelligence of children aged 5-6 years at PAUD Salsabila Tembung. This research is a type of research that uses a Pre-Exprimental research design in which there are still external variables that influence the forms of the dependent variable. The form of design used is One-Group Pretest-Posttest Design, in this study there is a group that is given treatment, then intends to compare the situation before and after treatment. The subjects of this study were 30 children, consisting of 16 boys and 14 girls. The instrument used in this study is an observation sheet for playing jumping words on the development of children's linguistic intelligence in accordance with the indicators to be achieved. This study uses quantitative analysis techniques in obtaining data. The data analysis technique uses statistical tests, namely the data normality test and hypothesis testing using the t-test. Thitung = 5.2195> Ttabel = 1.697, and because dk = (n-1) = (30-1) = 29 and the real level α = 0.05 so it can be concluded that Thitung> Ttabel (5.2195> 1.697) thus the hypothesis Ho is rejected and Ha is accepted. So it can be stated that there is a significant effect of playing jumping words on the linguistic intelligence of children aged 5-6 years at PAUD Salsabila Tembung T.A 2022-2023.